Private (institutional) schools: bridging social gaps in urban cities in Nepal? - Adhikari, Devendra; Pasa, Rajan Binayek (Research Nepal Journal of Development Studies, 2021)
The interest of parents in the urban cities in Nepal is tending towards enrolling their children in paid private (institutional) schools, rather than free public schools. This paper aimed at exploring the reasons behind growing craziness of the parents towards the private education system in Nepal. We adopted a critical paradigm, case study approach using in-depth interviews, and observation techniques to gather field information. This study has signaled that institutional schools are facilitating to homogenize the education system between haves and have nots groups in society. Different categories of private education systems, with accountable management team have facilitated in bridging the social gaps in Nepal. At the same time, public schools urgently need to revisit their management model, pedagogical system, and publicize their services and strengths, so that they could regain their trust from the urban parents. The explorations of this research could be helpful to outline the positive aspects of private schools and buildup the public education system along in Nepal.